Temperature-dependent functional response of the invasive Asian clam, Corbicula fluminea, feeding on natural phytoplankton. Issue 2 (3rd April 2021) - Rollwagen-Bollens, Gretchen; Bolam, Benjamin A.; Bollens, Stephen M.; Henricksen, Summer; Sandison, Carol; Zimmerman, Julie
ABSTRACT: The invasive suspension-feeding Asian clam, Corbicula fluminea, is abundant and broadly distributed in temperate rivers and lakes, yet its feeding dynamics, including how feeding rate varies as a function of prey density (i.e., functional response) and temperature, are not well known. We therefore undertook feeding experiments using adult C. fluminea and varying concentrations of natural phytoplankton prey (measured as chlorophyll a concentration). Clearance (filtration) rates adjusted to clam wet weight (WW) did not vary with food concentration at either 15.0 or 20.5 °C and averaged 57.5 and 167.6 mL g −1 WW h −1, respectively. Ingestion rate, however, increased linearly with increasing food concentration at both 15.0 and 20.5 °C. Both clearance rate and ingestion rate showed strong temperature dependence, with Q10 coefficient values of 6.99 and 5.65, respectively. These high feeding rates support the emerging view that this species is capable of extensive ecological impacts in both its native range and invaded habitats.